2016
DOI: 10.1159/000447720
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure of Black Overweight Women in South Africa Is Lower than of White Women

Abstract: Background: Overweight affects 65% of black South African women. Effective weight management requires accurate measurement or estimation of energy expenditure. Aims: The study aimed to determine, among overweight women, whether measured resting energy expenditure (REE) differs between black and white participants, and the performance of REE estimation equations. Methods: The REE of 44 black (age 39.6 ± 9.7 years, body mass index (BMI) 35.1 ± 6.2 kg/m2) and 41 white (age 38.0 ± 11.6 years, BMI 33.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
(62 reference statements)
3
10
0
Order By: Relevance
“…Regardless of factors contributing to REE, acknowledging differences in REE between population groups is essential for acceptable estimation of REE in the prevention and management of childhood obesity. Previous studies at our institution [16,17] identified a lower REE in the black than white population group, specifically for women, which may contribute to the high prevalence of overweight or obesity in black South African women [4]. Our study results suggest that sex-associated population differences in REE may only occur after middle childhood but prior to adulthood and constitutes a future research question.…”
Section: Population Groupsupporting
confidence: 49%
See 2 more Smart Citations
“…Regardless of factors contributing to REE, acknowledging differences in REE between population groups is essential for acceptable estimation of REE in the prevention and management of childhood obesity. Previous studies at our institution [16,17] identified a lower REE in the black than white population group, specifically for women, which may contribute to the high prevalence of overweight or obesity in black South African women [4]. Our study results suggest that sex-associated population differences in REE may only occur after middle childhood but prior to adulthood and constitutes a future research question.…”
Section: Population Groupsupporting
confidence: 49%
“…Com-parison of population groups with respect to REE, overall and within sex categories, was considered for sample size calculations. To detect a clinically relevant difference in REE of 75 kcal/day between groups and assuming a common SD of 84 kcal/day [16,17], a sample of 28 participants per group was calculated to have 90% power when using a two-sided two-group Student's paired t-test at the 0.05 level of significance. More accurate calculation of sample size before the onset of the study, and the estimation of oversampling requirements to overcome sampling challenges and non-compliance, were not possible since REE research in South.…”
Section: Study Design Population and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight and height were measured with a digital scale (Sensa 804; Seca) and a stadiometer (Seca), respectively. The standardised protocol followed for measurement of REE including pretesting of the metabolic cart, achieving and identifying steady state, body composition and anthropometry has been described previously 10 . All measurements were taken by trained dietitians.…”
Section: Methodsmentioning
confidence: 99%
“…For REE outcome variables, a quantile regression model with bootstrap estimates race/ethnicity by sex was employed with covariates (five models for REE adjusted for age plus (a) FFM, (b) FFMI, (c) FFM plus FM, (d) FFMI plus FMI and (e) height, respectively). The combinations for these models were guided by factors influencing REE of race/ethnic groups and the findings of our previous research 10 . Reliability/agreement of REE estimations was conceptualised in accordance with ‘GRRAS’ guidelines 12 .…”
Section: Methodsmentioning
confidence: 99%